Diagnostic Criteria of Recurrent Acute Rhinosinusitis: A Systematic Review. Issue 3 (May 2021) - Saltagi, Mohamad Z.; Comer, Brett T.; Hughes, Samuel; Ting, Jonathan Y.; Higgins, Thomas S.
Background: RARS is a challenging clinical phenomenon that affects many patients, and diagnostic criteria for this condition are not fully characterized in the literature. Objective: To examine diagnostic criteria for recurrent acute rhinosinusitis (RARS). Study Design: Systematic review. Methods: Cochrane, PubMed (MEDLINE), clinicaltrials.gov, EMBASE, Google Scholar, and Web of Science databases were queried for articles related to RARS dating from 1990 to present, according to PRISMA statement guidelines. Full text articles pertinent to the diagnostic criteria of RARS were included in this review. Inclusion criteria included articles specifically addressing RARS; studies with 3 or more patients; and articles in English. Results: A total of 1022 titles/abstracts potentially related to RARS were identified. Of these, sixty-nine full texts were selected for review, and 22 of these ultimately met inclusion criteria. The level of evidence was generally low. Studies and guidelines have used many different definitions for RARS diagnosis over the years based on symptomatology, physical examination, nasal endoscopy, imaging, and laboratory domains. Clinically important RARS has been defined most commonly as 4 or more discrete episodes of ARS per year, but this frequency is typically based on expert opinion. Additionally, radiologic anatomic associations such as concha bullosa, accessory maxillary os, and narrowed infundibular distance may be associated with RARS. Endoscopic visualization and imaging are sometimes used to confirm the presence of sinus disease during exacerbations of RARS, but there is variability in this practice. Conclusion: The diagnostic definition for RARS has developed over time and is currently based on low level 4 and 5 evidence. Because of the migratory definition of RARS, comparing inter-study results of RARS management remains difficult, and future studies should aim to follow current expert guidelines on diagnostic criteria of RARS.